How Digital Transformation Impacts Customer Experience in the Hard Luxury Industry: Consensus on Omnichannel Strategy - Marine Bertrand; Ekaterina Glebova (Athens Journal of Business & Economics)
Despite the impact of digitalization in the luxury industry since the health crisis, few researches have been done on the hard luxury industry. Therefore, the aim of this study is to provide insight on how digitalization has been transforming the customer experience in this niche market. The study delivered additional insights to the existing literature, especially on the change in the digital strategy of hard luxury brands which tend to focus on an omnichannel approach. Through the analysis of interview data and a qualitative survey with some Kering experts on client service, the study deepens the new vision of digital customer experience and their perception of the client-centric approach in the luxury industry. The qualitative research highlights concrete actions that can be done by hard luxury brands in order to enhance the customer experience. Despite the challenges these brands face in preserving the values of this industry, such as craftsmanship and scarcity, the digital transformation has its share of opportunities. The results show a tendency to opt for omnichannel strategy, and the use and optimization of data and digital innovations to leverage the customer experience. In this study, a gap in the literature is addressed by focusing on the hard luxury segment and how digitalization has been transforming it.